Embodied Cognition in Performance: The Impact of Michael Chekhov’s Acting Exercises on Affect and Height Perception - Olenina, Ana Hedberg; Amazeen, Eric L.; Eckard, Bonnie; Papenfuss, Jason (Frontiers in Psychology, 2019)
Modern embodied approaches to cognitive science overlap with ideas long explored in theater. Theorists and instructors have emphasized the importance of movement in creating the necessary psychological states for embodying a character or inhabiting a fictional space. However, these connections have not been investigated scientifically. In the present study, participants performed 3 sets of exercises adapted from Michael Chekhov (1953), an influential early 20th-century performance theorist. Following the exercises, the participants’ affect (pleasantness and arousal) and self-perceptions of height were measured. There were significant effects of exercise on affect with pleasantness increasing after the expanding exercises, and arousal increasing after the contracting exercises. Although exercise only produced small, non-significant, changes in perceived height, there was a significant relation between perceived height and affect in which perceived height increased with increases in both pleasantness and arousal. These findings support the embodied approaches to acting advocated by Chekhov and others.